Forkhead box protein O1 (FoxO1) /SERPINB1 ameliorates ROS production in diabetic nephropathy. Issue 1 (20th December 2020) - Liang, Xiaoya; Su, Yanjin; Huo, Yongbo
Abstract: With the increasing prevalence of diabetes in recent years, diabetic nephropathy (DN) has become a severe disease that greatly threatens human health. DN not only is a common complication of diabetes, but also takes an important place in kidney disease. To this end, the present study was designed to explore the effects of Forkhead box protein O1 (FoxO1) on reactive oxygen species (ROS) production in DN mice. DN mice were treated with recombinant protein of FoxO1. Afterward, inflammation ELISA kits were used to measure the levels of TNF‐α, IL‐1β, IL‐6, and IL‐18. The levels of MDA, SOD, GSH, and GSH‐PX were measured using kits according to the manufacturer's instructions. In addition, the production of ROS was assessed. Interestingly, the expression of FoxO1 was down‐regulated in DN mice. The treatment of FoxO1 recombinant protein ameliorated MDA levels, increased the levels of SOD, GSH, and GSH‐PX, and induced both mRNA and protein expression of hepatic serine protease inhibitor B1 (serpinB1) in ND mice. Similarly, FoxO1 reduced MDA levels and ROS production, increased the levels of SOD, GSH, and GSH‐PXs, and induced the mRNA and protein expression of serpinB1 in in vitro model of DN. The inhibition of serpinB1 attenuated the effects of FoxO1 on ROS production‐induced oxidative stress in in vitro model of DN. Overall, FoxO1/SERPINB1 ameliorated ROS production‐induced oxidative stress in DN. Abstract : Taken together, the results showed that FoxO1/SERPINB1 ameliorates ROS production—induced oxidative stress in diabetic nephropathy vivo or vitro model. The present study provides some ideas for FoxO1/SERPINB1 that can relieve the symptoms of ROS production in diabetic nephropathy.